Science and Vedic Spirituality in Literary Terms of Swami Ji: Exploring the Link between Spiritual Progress and Social Change in the context of Swami Vivekananda (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Swami Vivekananda was essentially a Spiritual ace. So certainly he looked each change through the eye of otherworldliness. To him each change was nevertheless a push to show the heavenly profound guideline. It didn't have any effect to him whether that celestial rule was inside or outside. To state as such, regardless of whether it was menifestation of Atman as an individual perfect rule or whether it was manfestation of Brahman, the cosmological awesome standard—vyashti or samashti rule, he generally attempted to achieve Spiritual advance in individual and group.To this end he has stated, All solid social changes are indications of the profound powers working inside and if these are solid and balanced, society will organize itself as needs be. Every individual needs to work out his own answer there is no other way, thus likewise with countries. Once more, the immense establishments of each country are the states of its extremely presence and can't be changed by the form of some other race. Until the point when higher organizations have been developed, any endeavor to break the old ones will be awful. Development is constantly slow.